Penyuluhan higiene, sanitasi dan keselamatan kerja di laboratorium pengolahan pangan - Rokhima, Ainur; Fadhiila, Indah Tentamia Hanaa; Apriliawan, Pinky; Zurinah, Silva; Ulilalbab, Arya; Swandono, Hari Untarto (Jurnal PADE: Pengabdian & Edukasi, 2025)
Health, occupational safety, and hygiene and sanitation are important aspects related to food service. This aspect affects the quality of food and the safety of students so that the food can be consumed safely. Efforts made to emphasize hygiene, sanitation and work safety include education in the form of counseling. This counseling aims to determine the effectiveness of lecture and discussion methods in enhancing information related to health and safety at work, hygiene, and sanitation among food handlers. Efforts to emphasize occupational safety, hygiene, and sanitation include education through outreach conducted at Vocational Senior High School Subulus Salam, Pagu sub-district, Kediri District on July 30 from 9:00 to 11:00 AM. This counseling uses the pretest-posttest method with a sample of twenty-five food handlers. The questionnaire is used in the process of collecting pre-test and post-test results to educate students about hygiene and sanitation in the Food Processing Laboratory at Vocational Senior High School Subulus Salam. The results of the pre-test showed that the average score obtained by the students was 74.7. Meanwhile, in the post-test, the average score of the students increased to 80.1. The conclusion of this outreach shows that students' scores on pre- and post-tests regarding hygiene, sanitation, and workplace safety in the laboratory increased. It is hoped that with the knowledge gained, participants will be able to understand and apply hygiene, sanitation, and occupational safety in the laboratory.